Meckel's Diverticulum in Crohn's Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Meckel's diverticulum is a congenital abnormality of the distal ileum associated with failed vitelline duct closure. Detailed pathological studies have estimated its frequency to be about 2% of the general population, and it has been anecdotally recorded in patients with Crohn's disease. Most patients with Crohn's disease have imaging studies of the small intestine during the course of their disease, and often, an intestinal resection. Thus, it seems possible to estimate the prevalence of Meckel's diverticula in Crohn's disease. In addition, patient characteristics may be important, especially if management of Crohn's disease is altered. Of 877 patients with Crohn's disease, 10 (about 1%) had a Meckel's diverticulum diagnosed, including six men and four women. All were diagnosed with Crohn's disease before age 50 years and seven were diagnosed before age 30 years. There were five with ileocolonic disease, two with colon-only disease and three with ileum-only disease. The clinical behaviour of five patients could be classified as penetrating and two as stricturing. A total of 311 patients had an ileocolonic resection, including eight (about 2%) with a Meckel's diverticulum. In contrast to some case reports, no heterotopic mucosa was detected and the Meckel's diverticulum was incidental and, apparently, an unexpected finding. In each case, the diverticulum was not involved with Crohn's disease but was included in the ileal resection. These results suggest that the overall prevalence of a Meckel's diverticulum is not increased in Crohn's disease but may result in resection of additional small intestine.